Construction of optical system for an atomic clock-beyond atomic fountain - Wang, Xiumei; He, Jin; Wang, Yifei; Wang, Yunjia; Wang, Wenming; Wang, Weili; Li, Shiguang; Zhu, Xi; Liu, Guodong; Liu, Shuo; Wang, Ye; Wang, Liang; et al. (Frontiers in Physics, 2022)
We demonstrate the construction of the optical system in beyond fountain based on 87Rb atom. The optical system includes a high-stability laser system and an optical lattice. The high-stability laser system with a new scheme of frequency locking and shift is introduced in detail, which is an important laser source for laser cooling and trapping. The optimized frequency and intensity stability are achieved to 4E-14*tao^（-1/2）and 4E-5*tao^（-1/2, respectively, which are highly stable. On the basis of conventional atomic fountain clock, the optical lattice is specially investigated along the direction of gravity and its characteristics are studied systematically. For the optimized and novel exploration, we predict the achievable stability of 3.6E-14*tao^（-1/2）and it has the potential to be improved to 3.6E-15*tao^（-1/2） in future. The realizability of this construction due to stabilized laser and optical lattice makes the beyond fountain promising candidate for the next-generation high performance microwave atomic clock.